2013
DOI: 10.3389/fpls.2013.00380
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated links between detritivores and aboveground herbivores

Abstract: Most studies on plant-mediated above–belowground interactions focus on soil biota with direct trophic links to plant roots such as root herbivores, pathogens, and symbionts. Detritivorous soil fauna, though ubiquitous and present in high abundances and biomasses in soil, are under-represented in those studies. Understanding of their impact on plants is mainly restricted to growth and nutrient uptake parameters. Detritivores have been shown to affect secondary metabolites and defense gene expression in abovegro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
(30 reference statements)
1
25
0
Order By: Relevance
“…The organic farming system has recorded the highest diversity index (0.61) followed by integrated (0.57) and least in conventional farming (0.51) Table 3. The present findings are supported by many workers (Schrader et al, 2006;Santigo et al, 2009;Naureen et al, 2010;Carlos et al, 2011;Parwez and Abbas, 2012;Wurst, 2013 was found that organically maintained fields showed higher taxa richness, abundance and diversity of the soil faunal community. In turn, it also enhances the level of soil organic carbon, availability of nutrients that may contribute to the long term functional approach in an agro-ecosystem.…”
Section: Macro Arthropodssupporting
confidence: 80%
“…The organic farming system has recorded the highest diversity index (0.61) followed by integrated (0.57) and least in conventional farming (0.51) Table 3. The present findings are supported by many workers (Schrader et al, 2006;Santigo et al, 2009;Naureen et al, 2010;Carlos et al, 2011;Parwez and Abbas, 2012;Wurst, 2013 was found that organically maintained fields showed higher taxa richness, abundance and diversity of the soil faunal community. In turn, it also enhances the level of soil organic carbon, availability of nutrients that may contribute to the long term functional approach in an agro-ecosystem.…”
Section: Macro Arthropodssupporting
confidence: 80%
“…In addition to these proven growth-promoting effects (e.g. van Groenigen et al, 2014), recent studies have highlighted that earthworms can also benefit plants by increasing their ability to resist herbivore attacks (Lohmann, Scheu, & Muller, 2009;Trouve, Drapela, Frank, Hadacek, & Zaller, 2014;Wurst, 2013;Wurst, Allema, Duyts, & Van Der Putten, 2008).…”
mentioning
confidence: 99%
“…Biotic interactions of plants induce phenotypic changes in plants, and a wide range of local plant responses to organisms above and below the ground can systemically affect the whole plant. There are many examples of below-ground interactions affecting above-ground plant tissues and vice versa (reviewed by, e.g., van Dam et al 2003;Bezemer & van Dam 2005;Wurst 2013). For example, root herbivory by wireworms can affect secondary metabolites in leaves (Wurst et al 2008), and shoot herbivory by caterpillars may change secondary metabolites in roots (Soler et al 2007a).…”
Section: Zones Of Influence Of Plants Affected By Aboveand Below-groumentioning
confidence: 99%
“…These plant-mediated interactions between below-ground and above-ground organisms have been studied intensively in the last two decades, and several reviews were published on the topic. Since 1993, when the first conceptual model on plant-mediated interactions between root and shoot herbivores was published (Masters, Brown & Gange 1993), reviews have focussed on the role of changes in plant physiology (mainly plant defence) in mediating indirect interactions between above-ground insect herbivores and root herbivores (van Dam et al 2003;van Dam & Heil 2011;Soler, Erb & Kaplan 2013), soil micro-organisms such as mycorrhizal fungi (Gehring & Whitham 1994;Koricheva, Gange & Jones 2009;Hartley & Gange 2009;Zamioudis & Pieterse 2012), and detritivores (Wurst 2010(Wurst , 2013. Other reviews considered the role of above-below-ground linkages in a global context (De Deyn & Van der Putten 2005), for ecosystem processes such as plant succession and biological invasions (van der Putten et al 2009;Harvey, Bukovinszky & van der Putten 2010), and to predict the impact of global change (van der Putten et al 2009).…”
Section: Introductionmentioning
confidence: 99%